Potentiating the anti-cancer profile of tamoxifen-loaded graphene using deep eutectic solvents as functionalizing agents - Zainal-Abidin, Mohamad Hamdi; Hayyan, Maan; Ngoh, Gek Cheng; Wong, Won Fen; Looi, Chung Yeng (Springer Verlag, 2020)
Deep eutectic solvents (DES) are an alternative to conventional functionalizing agents. These neoteric functionalizing agents have been reported to improve the dispersibility and biocompatibility of graphene in the cellular environment. DES-functionalized graphene also has significantly greater tamoxifen (TAM)-loading capacity than non-functionalized graphene. Therefore, this study investigated the anti-cancer properties of TAM-loaded graphene against cancerous cells. TAM-loaded, DES-functionalized graphene showed a significant increase in anti-cancer activity, especially in the case of DES ChCl:fructose (2:1), as validated by cell viability, reactive oxygen species, and cell cycle progression assays. The cytotoxicity profile of TAM-loaded graphene against cancerous cells was confirmed by real-time cell growth analysis. Across all tested cellular kinetic models, the most significant reduction in the growth rate constant of cancerous cells was obtained using graphene functionalized with DES ChCl:fructose (2:1). All told, DES-functionalized graphene demonstrated improved anti-cancer activity compared to non-functionalized graphene. © 2019, King Abdulaziz City for Science and Technology.